PENGELOLAAN LINGKUNGAN BELAJAR OUTDOOR PADA SEKOLAH BERLAHAN SEMPIT: OUTDOOR LEARNING MANAGEMENT IN LAND-CONSTRAINED SCHOOLS - Sari, Dianti Yunia; Maulani, Susan; Irma, Ade (Universitas Islam Malang, 2024)
This research is for using the outdoor preschool. Because environment for learning have minimize land. The research topic wants to comprehend how schools with minimize land handle outdoor learning areas. This type of research uses a case study approach and is qualitative. The principal of the school and the instructors of RA Nurul Ikhwan gave data for this research by interviews, observations, and documentation methods. Data reduction, visualisation, and verification are a few of data analysis approaches used in this research. The results of this research argue that environment at RA Nurul Ikhwan located in a small area, involves setting up the implementation of outdoor learning environment management that matches with enough safety regulations, planning for the management of the outdoor learning environment, and motivating teachers to implement learning environment management. Designed outside area and keeping attention on kids when they join in activities in the outdoor learning area. It is intended that by setting the management of the outdoor learning environment into practice, teachers and school principals will be able to create and maintain improvements that will make the environment better in the future.